PWE-168 Omega-3 fatty acid infusion reduces gastrointestinal toxicity and prevents thromboembolism in patients with advanced oesophagogastric cancer treated with palliative platinum based chemotherapy. (22nd June 2015) - Eltweri, AM; Thomas, A; Dennison, A; Metcalfe, M; Bowrey, D
Abstract : Introduction: The omega-3 fatty acids, EPA and DHA have proven anticancer activity in laboratory and clinical cancer studies. This clinical trial evaluated whether adding omega-3 fatty acids to palliative platinum based chemotherapy influenced the outcome of patients with oesophagogastric cancer compared to those given chemotherapy alone Method: 21 participants in the 1st stage of a phase II single arm trial received palliative chemotherapy, intravenous (IV) epirubicin (50mg/m 2 ) and oxaliplatin (130mg/m 2 ) every 21 days, oral capecitabine (1250mg/m 2 ) daily for 21 days and IV omega-3 fatty acids (2ml/Kg/4 h) (Omegaven® Fresenius-Kabi). The Omegaven infusion was given immediately after the chemotherapy on days 1, 8 and 15 of each cycle (intervention). Clinical outcomes were compared to outcomes in 37 patients treated with chemotherapy alone (control). Toxicities were graded using the CTCAE v4.03. Clinical response rate was assessed by RECIST v1.1 criteria. Results: Fifty-six patients eligible participants were screened for inclusion, 35 were excluded principally because of poor performance status. Twenty one patients were enrolled in the study, 20 received at least one treatment and they form the basis of this report. The radiological response and toxicity of the intervention and control groups are indicated (Table 1 ). The mean baseline and 7 day post treatment triglyceride levels were 1.7 mmol/l (95% CI 1.6- 1.79) and 1.66 mmol/l (95% CI 1.56–1.75) respectively. The highest recorded triglyceride level was 4.84 mmol/l. No patient experienced fat overload syndrome or grade 3/4 hypertriglyceridemia. Mean platelet counts were 217 X109/l in the intervention group (95% CI 207–226 X109/l) compared to 332 X109/l in the control group (95% CI 316–348 X109/l). Conclusion: Compared to patients treated with chemotherapy alone, those treated with supplementary omega-3 fish oils had reduced chemotherapy related toxicity, notably fewer gastrointestinal and thromboembolic adverse effects. Omega-3 fatty acids have the potential to ameliorate the toxicity associated with chemotherapeutic agents. Disclosure of interest: A. Eltweri Grant/ Research Support from: Fresenius-Kabi, A. Thomas Grant/ Research Support from: Fresenius-Kabi, A. Dennison Grant/ Research Support from: Fresenius-Kabi, M. Metcalfe Grant/ Research Support from: Fresenius-Kabi, D. Bowrey Grant/ Research Support from: Fresenius-Kabi, Nutricia